A Retrospective Paired Comparison Between Untargeted Next Generation Sequencing and Conventional Microbiology Tests With Wisely Chosen Metagenomic Sequencing Positive Criteria - Qin, Hanyu; Peng, Jinmin; Liu, Ling; Wu, Jing; Pan, Lingai; Huang, Xiaobo; Huang, Man; Qiu, Haibo; Du, Bin; , The China Critical Care Clinical Trials Group (CCCCTG) (Frontiers in Medicine, 2021)
Objectives: To evaluate the performance of metagenomic next generation sequencing (mNGS) using adequate criteria for the detection of pathogens in lower respiratory tract (LRT) samples with a paired comparison to conventional microbiology tests (CMT). Methods: One hundred sixty-seven patients were reviewed from four different intensive care units (ICUs) in mainland China during 2018 with both mNGS and CMT results of LRT samples available. The reads per million ratio (RPMsample/RPMnon−template−control ratio) and standardized strictly mapped reads number (SDSMRN) were the two criteria chosen for identifying positive pathogens reported from mNGS. A McNemar test was used for a paired comparison analysis between mNGS and CMT. Results: One hundred forty-nine cases were counted into the final analysis. The RPMsample/RPMNTC ratio criterion performed better with a higher accuracy for bacteria, fungi, and virus than SDSMRN criterion [bacteria (RPMsample/RPMNTC ratio vs. SDSMRN), 65.1 vs. 55.7%; fungi, 75.8 vs. 71.1%; DNA virus, 86.3 vs. 74.5%; RNA virus, 90.9 vs. 81.8%]. The mNGS was also superior in bacteria detection only if an SDSMRN ≥3 was used as a positive criterion with a paired comparison to culture [SDSMRN positive, 92/149 (61.7%); culture positive, 54/149 (36.2%); p < 0.001]; however, it was outperformed with significantly more fungi and DNA virus identification when choosing both criteria for positive outliers [fungi (RPMsample/RPMNTC ratio vs. SDSMRN vs. culture), 23.5 vs. 29.5 vs. 8.7%, p < 0.001; DNA virus (RPMsample/RPMNTC ratio vs. SDSMRN vs. PCR), 14.1 vs. 20.8 vs. 11.8%, p < 0.05]. Conclusions: Metagenomic next generation sequencing may contribute to revealing the LRT infection etiology in hospitalized groups of potential fungal infections and in situations with less access to the multiplex PCR of LRT samples from the laboratory by choosing a wise criterion like the RPMsample/RPMNTC ratio.